High temperature coatings - Bose, Sudhangshu (Elsevier Butterworth-Heinemann, 2007)
High Temperature Coatings demonstrates how to counteract the thermal effects of the rapid corrosion and degradation of exposed materials and equipment that can occur under high operating temperatures. This is the first true practical guide on the use of thermally-protective coatings for high-temperature applications, including the latest developments in materials used for protective coatings. It covers the make-up and behavior of such materials under thermal stress and the methods used for applying them to specific types of substrates, as well as invaluable advice on inspection and repair of existing thermal coatings. With his long experience in the aerospace gas turbine industry, the author has compiled the very latest in coating materials and coating technologies, as well as hard-to-find guidance on maintaining and repairing thermal coatings, including appropriate inspection protocols. The book will be supplemented with the latest reference information and additional support for finding more application-type and industry-type coatings specifications and uses, with help for the reader in finding more detailed information on a specific type of coating or a specific type of use. Offers overview of the underlying fundamental concepts of thermally-protective coatings, including thermodynamics, energy kinetics, crystallography, and equilibrium phases Covers essential chemistry and physics of underlying substrates, including steels, nickel-iron alloys, nickel-cobalt alloys, and titanium alloys Provides detailed guidance on wide variety of coating types, including those used against high temperature corrosion and oxidative degradation, as well as thermal barrier coatings.